Profile and analysis of diabetes chronic complications in Outpatient Diabetes Clinic of Cipto Mangunkusumo Hospital, Jakarta (Medical Journal of Indonesia, 2015)
Background: Chronic complications of diabetes mellitus have a significant role in increasing morbidity, mortality, disability, and health cost. In the outpatient setting, the availability of data regarding to the chronic complications of type 2 diabetes is useful for evaluation of prevention, education, and patientâs treatment. This study aimed to describe the characteristic of type 2 diabetes chronic complications in outpatient diabetes clinic.Methods: A cross-sectional study was done using 155 patients in Outpatient Diabetes Clinic of Cipto Mangunkusumo Hospital (RSCM), Jakarta in 2010. Secondary data were used from medical record based on history taking, physical examination, diabetic foot assessment, laboratory, neurologic, cardiology, opthalmology, ankle brachial index, and electrography of the patients. Characteristic profiles of the subjects, prevalence of the chronic complications, and its association with diabetes risk factors, such as glycemic control using HbA1c, fasting blood glucose, duration of diabetes, and LDL cholesterol were analyzed using chi square test.Results: Among 155 subjects participated in the study, most of them were women (59%) and elderly (46%). The prevalence of diabetes chronic complications was 69% from all subjects. These chronic complications included microangiopathy, macroangiopathy and mixed complications, with prevalence of 56%, 7% and 27% respectively. Microangiopathy included nephropathy (2%), retinopathy (7%), neuropathy (38%) and mixed complications (53%). Macroangiopathy included coronary heart disease (46%), peripheral arterial disease (19%), stroke (18%), and mixed complication (17%). From the analysis, we found significant association between duration of diabetes and diabetic neuropathy (p = 0.003).Conclusion: Prevalence of diabetes chronic complications in Outpatient Diabetes Clinic of Cipto Mangunkusumo Hospital, mainly dominated by microvascular-related complications including nephropathy, retinopathy, neuropathy and mixed complications. There was statistical significance between diabetes duration and diabetic neuropathy.